How to choose an organization pattern in the innovation of the complex product systems: findings from fsQCA - Jie Hou; Meili Zhang; Kaodui Li; Zeyu Xing (Humanities & Social Sciences Communications)
Abstract In the innovation of the complex product systems (CoPS), the choice of organization patterns becomes the decision of whether innovation subjects can promote innovative development. Based on the dynamic capability theory, we take 184 firms participating in the Internet of Things (IoT) product system as a sample, and use fsQCA approach for the first time to explore conditional configurations of realizing the innovation of the CoPS, so as to provide a way for innovation subjects to choose suitable organization patterns. The results find that the realization of innovation performance (IPF) of the CoPS is the result of multiple factors, and an isolated factor is not enough to explain it. There are four equivalent ways to achieve IPF, containing three organization patterns. Namely, the modular-oriented organization pattern, the integration-oriented organization pattern, and the relationship-oriented organization pattern. Integration capability and modularity capability as core competencies, and internal cooperation and external coordination as external resources, are important supports for innovation subjects of the CoPS to achieve innovative development. In the integration-oriented organization pattern, there is a substitute relationship between modularity capability and internal cooperation under certain conditions. This work has a certain theoretical contribution to extend the dynamic capability theory to the theoretical system of the innovation of the CoPS, and also provides a rich practical enlightenment for innovation subjects how to choose organization patterns in the innovation of the CoPS.